Simulation Study on Geometric Parameters Influencing the Flow Coefficient of Perforated Plate - Yaogen Peng; Huijun Mao; Zhichao Liu; Cheng Wei (Buildings, 2023)
Natural ventilation is one of the vital means for passive energy-efficient design in green buildings. As a widely used building façade, the perforated plate is mostly utilized for appearance decoration, noise absorption, and sun shading, but its impact on the natural ventilation effect has rarely been paid attention to. In this study, the influence of the perforation rate, the perforation size, and the perforation shape on the flow coefficient of the perforated plate were simulated using the commercial CFD software Fluent, and the correlation between the flow coefficient and these geometric parameters was then regressed. The results show that the flow coefficient of perforated plate increases with the increase in perforation rate, which is slightly greater than that of ordinary building openings, and the corresponding flow coefficients of different holes rank as circle > square > triangle under the same conditions. The flow coefficient increases with the increase in the perforation size, and this effect is greater when the size is small. In addition, the flow coefficient is less affected by the size of round holes compared to triangular and square holes. The regression model indicates that both the perforation rate and the perforation size have a considerable positive influence on the flow coefficient, while the square and triangle holes have a negative influence on the flow coefficient compared with the circular hole. Moreover, the geometric parameters of perforated plates that have the greatest influence on flow coefficient are perforation rate, perforation shape, and size, in descending order.